Grafting of some monomers onto cellulose and determination of metal and water uptake properties - Cankaya, Nevin; Temuz, M. Mursit (Editura Academiei Romane, 2015)
Some new cellulosic materials with water uptake capacity and being suitable for the sorption of metal ions were synthesized by the grafting of cellulose with monomers, such as N-(4-nitrophenyl)acrylamide (4NPA), N-cyclohexylacrylamide (NCA), 4-vinylpyridine (4VP), acrylamide (AM), methacrylamide (MAM), diacetoneacrylamide (DAAM), methylmethacrylate (MMA) and diallylamine (DA). Firstly, cellulose methacrylate (Cell.met) was prepared by esterification of the primary-OH group of cellulose with methacryloyl chloride with a 21.3% yield by mole. The monomers were grafted into cellulose methacrylate via free radical polymerization using 2,2'-azobisisobutyronitrile (AIBN) as an initiator in acetonitrile. The graft copolymers were characterized by FT-IR spectra, elemental analyses and thermal analysis. The thermal stabilities of the graft copolymers were determined by the TGA method and it was established that the thermal stability of the copolymers decreased with grafting. The water uptake capacity of 8 graft copolymers and their metal ion sorption tendency (Ni2+, Co2+ Cu2+, Cd2+, Pb2+, Fe2+ and Cr2+) were found to improve with grafting.
Keywords: Cellulose; Graft copolymer; Metal ion and water uptake